6.1k views
5 votes
Find the difference (9x2 + 3x – 2) + (3x2 – 5x – 3) Please show work so I can see what I was doing wrong. Thanks

User Mia Clarke
by
5.0k points

2 Answers

4 votes

Answer:

12x²- 2x -5

Explanation:

actually this is the sum

(9x² + 3x – 2) + (3x² – 5x – 3)=

9x² + 3x – 2 + 3x² – 5x – 3=

(9+3)x² + (3-5)x- 5 = 12x²- 2x -5

User Jeeyoung Kim
by
5.7k points
1 vote

Answer:

Adding the x² terms gives us 9x² + 3x² = 12x², combing the x terms gives us 3x - 5x = -2x and -2 - 3 = -5 so the answer is 12x² - 2x - 5.

User Linuts
by
5.2k points